2015
DOI: 10.1097/prs.0000000000001414
|View full text |Cite
|
Sign up to set email alerts
|

The Posteromedial Thigh Flap for Head and Neck Reconstruction

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Mojallalal et al [10] have described the constancy of the location of the d-SFAP flap perforator at a mean distance of 22.79 ± 1.55 cm from the pubic tubercle and in close relation with the saphenous vein, which is comparable to the mean distance of 20.5 ± 3.17 cm in our study. Our data are also consistent with other studies that have found most of the perforators of the PAP flap located 8-10 cm from the pubic crease [3].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mojallalal et al [10] have described the constancy of the location of the d-SFAP flap perforator at a mean distance of 22.79 ± 1.55 cm from the pubic tubercle and in close relation with the saphenous vein, which is comparable to the mean distance of 20.5 ± 3.17 cm in our study. Our data are also consistent with other studies that have found most of the perforators of the PAP flap located 8-10 cm from the pubic crease [3].…”
Section: Discussionsupporting
confidence: 93%
“…The PAP flap has become an ideal choice for autologous tissue breast reconstruction as an alternative to the deep inferior epigastric perforator flap [15]. However, there are few reports regarding its use for intraoral reconstruction [3,4,5]. The main concern in our population could be its greater thickness compared to the ALT flap, but with our results, we can show that there is not much difference when the PAP flap is designed around a distal perforator.…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, the ALT free flap is the most commonly used among all thigh flaps for tongue reconstruction. Three previous case series on the use of PAP flaps for head and neck reconstruction have been from Taiwan (Fernández‐Riera et al, ; Scaglioni et al, ; Wu et al, ), and one case series of eight patients from the United States (Mayo, Canizares, Torabi, Allen, & St Hilaire, ). In this case series, Mayo et al describe the versatility of this flap for various reconstructions, but only two were in the extraoral head and neck region and they did not report any PAP flap for intraoral reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the profunda artery perforator (PAP) flap, harvested from the posteromedial region of the thigh, has been proposed as a good choice for use in tongue reconstruction (Fernández-Riera, Hung, Wu, & Tsao, 2017;Scaglioni, Kuo, Yang, & Chen, 2015;Wu et al, 2016). In Western countries, thigh flaps, especially the PAP flap, are less frequently used than in Asian countries for tongue reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Bulky flaps assuring palatal‐glossal contact, such as the rectus abdominus (RA) and the anterolateral (ALT) free flaps, are among the most popular reconstructive options worldwide (Chepeha, 2010; Han et al, 2019). Recently, the profunda artery perforator (PAP) flap, harvested from the posteromedial region of the thigh, has been proposed as a good choice for tongue reconstruction (Fernández‐Riera et al, 2017; Heredero et al, 2019; Scaglioni et al, 2015; Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%